2015
DOI: 10.1002/etc.2951
|View full text |Cite
|
Sign up to set email alerts
|

Polyparameter linear free energy relationship for wood char–water sorption coefficients of organic sorbates

Abstract: Black carbons (BCs), including soots, chars, activated carbons, and engineered nanocarbons, have different surface properties, but we do not know to what extent these affect their sorbent properties. To evaluate this for an environmentally ubiquitous form of BC, biomass char, we probed the surface of a well-studied wood char using 14 sorbates exhibiting diverse functional groups and then fit the data with a polyparameter linear free energy relationship (ppLFER) to assess the importance of the various possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 40 publications
0
26
1
Order By: Relevance
“…As discussed earlier, the biochar and GAC/CNT differ in that biochar generally contains a large amount of organic/inorganic impurities, which complicates the interactions between the biochars and the adsorbed chemicals. Among the descriptors, the E , S , B , V , and BET are the dominant ones for biochars, agreeing with the reported MLR models in which the S , B , and V are the most important (BET and V t are not included in the reported MLR models). ,, The coefficient for E is not recognized as significant; this may be because the adsorption data are only available for 1 biochar and 14 chemicals . The dependency on E may emerge if the data set is to be expanded in both chemicals and adsorbents.…”
Section: Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As discussed earlier, the biochar and GAC/CNT differ in that biochar generally contains a large amount of organic/inorganic impurities, which complicates the interactions between the biochars and the adsorbed chemicals. Among the descriptors, the E , S , B , V , and BET are the dominant ones for biochars, agreeing with the reported MLR models in which the S , B , and V are the most important (BET and V t are not included in the reported MLR models). ,, The coefficient for E is not recognized as significant; this may be because the adsorption data are only available for 1 biochar and 14 chemicals . The dependency on E may emerge if the data set is to be expanded in both chemicals and adsorbents.…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, the calculations showed that their contributions varied within a broad range (Figure S16), so the adsorbent properties cannot be neglected in the adsorption prediction. This can explain part of the higher deviations in commonly used MLRs as the absence of adsorbent properties has failed to capture the differences in the adsorption among the adsorbents, even if they belong to the same class. ,, …”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations